Organic sulfur oxidation to sulfate in soil samples for total sulfur determination by turbidimetry - Rossete,Alexssandra Luiza Rodrigues Molina (2008)
Sulfur in the soil occurs in two basic forms, organic and inorganic S. The organic form accounts for 95 % of S in most soils. The effectiveness of organic S to oxidate to sulfate was evaluated for total S determination in soil samples by wet (acid) and dry-ash (alkaline) oxidation methods. To evaluate the wet method and the possible use as a reference when evaluating the dry method proposed here, a reference standard from the US National Institute of Standards and Technology (NIST) was used (Montana Soil - NIST 2710). The dry-ash oxidation process with alkaline oxidizing agents is one of the simplest oxidation methods of organic S to the sulfate form and was compared with the wet process. The objective of the study was to develop a dry method that would be easy to apply and allow the complete conversion of organic S to sulfate in soil samples and later detection by turbidimetry. The effectiveness of organic S oxidation to sulfate was evaluated by means of three alkaline oxidation mixtures: NaHCO3 + Ag2O, Eschka mixture (17 % Na2CO3, 66 % MgO, and 17 % K2CO3), and NaHCO3 + CuO. The procedure to quantify the sulfate concentration was based on the reaction with barium chloride and turbidimetric detection. Sulfur quantification in the standard sample by the wet method proved adequate, precise and accurate. It should also be pointed out that no significant differences were found (95 % reliability) between the wet and dry processes (NaHCO3 and Ag2O oxidation mixture) in six different Brazilian soils. The proposed dry method can therefore be used in the preparation of soil samples for total S determination.